Caffeic Acid Phenethyl Ester Protects Blood–Brain Barrier Integrity and Reduces Contusion Volume in Rodent Models of Traumatic Brain Injury - Zhao, Jing (Mary Ann Liebert, Inc., 2012)
A number of studies have established a deleterious role for inflammatory molecules and reactive oxygen species (ROS) in the pathology of traumatic brain injury (TBI). Caffeic acid phenethyl ester (CAPE) has been shown to exert both antioxidant and anti-inflammatory effects. The primary objective of the present study was to examine if CAPE could be used to reduce some of the pathological consequences of TBI using rodent models. Male Sprague-Dawley rats and C57BL/6 mice were subjected to controlled cortical impact (CCI) injury. Blood–brain barrier (BBB) integrity was assessed by examining claudin-5 expression and the extravasation of Evans blue dye. The effect of post-injury CAPE administration on neurobehavioral function was assessed using vestibulomotor, motor, and two hippocampus-dependent learning and memory tasks. We report that post-TBI administration of CAPE reduces Evans blue extravasation both in rats and mice. This improvement was associated with preservation of the levels of the tight junction protein claudin-5. CAPE treatment did not improve performance in either vestibulomotor/motor function (tested using beam balance and foot-fault tests), or in learning and memory function (tested using the Morris water maze and associative fear memory tasks). However, animals treated with CAPE were found to have significantly less cortical tissue loss than vehicle-treated controls. These findings suggest that CAPE may provide benefit in the treatment of vascular compromise following central nervous system injury.